Numerical simulation of wall deformation in an aneurysm model - Ribeiro, J.E. (2018)
This work presents the numerical assessment of the deformation of an artery wall with and without an aneurism. The simulations consider the hyper-elastic behaviour of the artery tissues, taken in consideration the properties of polydimethylsiloxane (PDMS), which are more similar to the biological tissues. The numerical simulations were performed using the commercial finite element routines ANSYS®, by considering the inner the artery fluid flow and the consequent pressure is used to simulate the wall deformation.